Faktor Determinan Kejadian Anemia pada Remaja Putri di SMA Negeri 3 Jakarta tahun 2025: A Determining Factor of Anemia among Female Adolescents at State Senior High School 3 Jakarta in 2025 - Farah Zhafirah; Utami Wahyuningsih; Sintha Fransiske Simanungkalit (Amerta Nutrition, 2025)
Background: Adolescence is a transitional phase marked by increased nutritional needs. Anemia among adolescent girls is an important health problem that can influence growth, along with physical and mental performance. The 2023 Indonesian Health Survey reported that 15.5% of individuals aged 15-24 years were anemic. Limited knowledge of anemia and iron supplement tablets inadequate family support, and low Mid-Upper Arm Circumference (MUAC) contribute to the risk of anemia. Objectives: To analyze factors associated with anemia among adolescent girls at SMA Negeri 3 Jakarta. Methods: This research applied a quantitative approach with a cross-sectional method, involving 180 students from grades X and XI who were chosen using a stratified random sampling technique. Variables examined included MUAC status, knowledge of anemia, knowledge of iron supplementation tablets, and family support. The study collected data through questionnaires complemented by anthropometric measurement procedures. Determinant variables were identified using chi-square analysis and logistic regression methods. Results: Anemia was found in 43.0% of adolescent girls. Knowledge of iron supplementation tablets showed a significant association with anemia and was the most influential factor (p-value=0.002; OR=0.48). Conversely, MUAC status (p-value=0.12), knowledge of anemia (p-value=0.11), and family support (p-value=0.05) showed no significant association. Conclusions: Knowledge of iron supplementation tablets was observed to have a correlation with cases of anemia (p-value=0.032) and served as a determinant factor of anemia among adolescent girls. Mid-upper arm circumference (MUAC) status, knowledge of anemia, and family support showed no significant association with anemia incidence. Students with better knowledge regarding iron supplementation tablets were associated with a 52.0% lower probability of anemia than students with insufficient understanding, after controlling for other variables. Efforts to improve nutrition education and promote iron supplementation intake are crucial for anemia prevention.